2023
DOI: 10.7717/peerj.15231
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in gene expression and alternative splicing in the Chinese horseshoe bat

Abstract: Sexually dimorphic traits are common in sexually reproducing organisms and can be encoded by differential gene regulation between males and females. Although alternative splicing is common mechanism in generating transcriptional diversity, its role in generating sex differences relative to differential gene expression is less clear. Here, we investigate the relative roles of differential gene expression and alternative splicing between male and female the horseshoe bat species, Rhinolophus sinicus. Horseshoe b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
2
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 70 publications
4
2
2
Order By: Relevance
“…Consistent with the results of a recent study based on the RNA-seq data of liver and brain [40], we found two Y-linked genes (KDM5D and DDX3Y) specifically expressed in males' cochlear tissue in R. sinicus. In addition, DDX3Y was also detected to be a malespecific gene in R. affinis hainanus.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Consistent with the results of a recent study based on the RNA-seq data of liver and brain [40], we found two Y-linked genes (KDM5D and DDX3Y) specifically expressed in males' cochlear tissue in R. sinicus. In addition, DDX3Y was also detected to be a malespecific gene in R. affinis hainanus.…”
Section: Discussionsupporting
confidence: 92%
“…Compared to a recent study on sex differences in AS in the liver and brain of R. sinicus [40], we identified a smaller number of alternatively spliced genes (ASGs) in the cochlear tissue (over 1000 in [40] and less than 250 in this study, see Figure 3a). This mainly resulted from the different methods used between studies (rMATs in [40]; DEXSeq in this study).…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations